1997
DOI: 10.1021/jp971178j
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Interaction of the Strong Acids HCl, HBr, and HI with a Photoluminescing Porous Silicon Surface

Abstract: The influence of the strong acids HCl, HBr, and HI on the nitrogen laser-excited photoluminescence (PL) from a porous silicon (PS) surface is established. In contrast to the stabilizing effect of hydrochloric acid on a PS surface photoluminescing in doubly deionized water, HI almost completely quenches the photoluminescence. The effect of an HBr solution is intermediate. These observations focus attention on (1) the importance of ambient oxygen in the region of a photoluminescing sample and (2) the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Silicon surfaces treated in an oxidative environment, especially high surface area porous silicon (PS) surfaces which are formed in wafer scale through electrochemical etching, display a variety of photoluminescent (PL) emissions upon excitation with a diversity of ultraviolet, visible, and near-infrared light sources. These PL emissions, which have attracted considerable attention, are thought to originate from regions close to the treated silicon surface. , However, the origin of the PL is the source of some controversy as the efficiency and wavelength range of the emitted light can be affected by the physical and electronic structure of the surface, the nature of the etching solution, and the nature of the environment into which the etched sample is placed. In conjunction with detailed quantum chemical modeling of those fluorophors which might be present on a PS surface, , we have examined the derivatization 10,17 of this oxidizing surface. The results of these studies suggest that the commonly observed “orange−red” photoluminescence from a PS surface can be correlated with −OH or −OR bonded silanone-based silicon oxyhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon surfaces treated in an oxidative environment, especially high surface area porous silicon (PS) surfaces which are formed in wafer scale through electrochemical etching, display a variety of photoluminescent (PL) emissions upon excitation with a diversity of ultraviolet, visible, and near-infrared light sources. These PL emissions, which have attracted considerable attention, are thought to originate from regions close to the treated silicon surface. , However, the origin of the PL is the source of some controversy as the efficiency and wavelength range of the emitted light can be affected by the physical and electronic structure of the surface, the nature of the etching solution, and the nature of the environment into which the etched sample is placed. In conjunction with detailed quantum chemical modeling of those fluorophors which might be present on a PS surface, , we have examined the derivatization 10,17 of this oxidizing surface. The results of these studies suggest that the commonly observed “orange−red” photoluminescence from a PS surface can be correlated with −OH or −OR bonded silanone-based silicon oxyhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…The light-induced PL from PS has been associated with a variety of mechanisms, including emission from quantum-confined silicon crystallites, surface-localized states, ,, surface-confined defects , or surface-confined molecular or molecule-like emitters. The efficiency and wavelength range of the emitted light can be affected by the physical and electronic structure of the surface, the nature of the etching solution, ,, and the nature of the environment into which the etched sample is placed. …”
Section: Introductionmentioning
confidence: 99%
“…The efficiency and wavelength range of the emitted light can be affected by the physical and electronic structure of the surface, 3 the nature of the etching solution, 22,23,25 and the nature of the environment into which the etched sample is placed. [26][27][28] The environment-dependent behavior of a PS surface suggests the possibility that several common fluorescent dyes whose radiative lifetimes are of the order of nanoseconds might be made to interact with the PS surface so as to considerably improve its observed luminescence rate. Here, we report a series of experiments designed to evaluate the interaction of select fluorescent dyes with PS samples of varying porosity and photovoltaic response.…”
Section: Introductionmentioning
confidence: 99%
“…While the luminescence is thought to occur near the PS surface, 6,7 the source of the visible emission is controversial as the efficiency and wavelength range of the emitted light can be affected by the physical and electronic structure of the surface, 3 the nature of the etching solution, [8][9][10] and the nature of the environment into which the etched sample is placed. [11][12][13] The luminescence from PS has been attributed to quantum-confined electrons and holes in columnar structures or undulating wires, [14][15][16][17] surface localized states, 6,7,18 and surface confined molecular emitters. [19][20][21][22][23] The tenets of quantum confinement assert that the luminescence results from the radiative recombination of confined electrons and holes possibly in columnar structures or undulating wires.…”
Section: Introductionmentioning
confidence: 99%